Δ133p53α Protects Human Astrocytes from Amyloid-beta Induced Senescence and Neurotoxicity. (21st August 2022) - Ungerleider, Kyra; Beck, Jessica A.; Lissa, Delphine; Joruiz, Sebastien; Horikawa, Izumi; Harris, Curtis C.
Highlights: Aβ diminishes the expression of Δ133p53α and induces SASP in human astrocytes. Enhanced expression of Δ133p53α protects human astrocytes from SASP and DNA damage. Enhanced expression of Δ133p53α prevents astrocyte-mediated neurotoxicity. This study warrants investigation toward therapeutic application of Δ133p53α. Abstract: Cellular senescence is an important contributor to aging and age-related diseases such as Alzheimer's disease (AD). Senescent cells are characterized by a durable cell proliferation arrest and the acquisition of a proinflammatory senescence-associated secretory phenotype (SASP), which participates in the progression of neurodegenerative disorders. Clearance of senescent glial cells in an AD mouse model prevented cognitive decline suggesting pharmacological agents targeting cellular senescence might provide novel therapeutic approaches for AD. Δ133p53α, a natural protein isoform of p53, was previously shown to be a negative regulator of cellular senescence in primary human astrocytes, with clinical implications from its diminished expression in brain tissues from AD patients. Here we show that treatment of proliferating human astrocytes in culture with amyloid-beta oligomers (Aβ), an endogenous pathogenic agent of AD, results in reduced expression of Δ133p53α, as well as induces the cells to become senescent and express proinflammatory SASP cytokines such as IL-6, IL-1β and TNFα. Our data suggest that Aβ-induced astrocyte cellular senescence is associated with accelerated DNA damage, and upregulation of full-length p53 and its senescence-inducing target gene p21 WAF1 . We also show that exogenously enhanced expression of Δ133p53α rescues human astrocytes from Aβ-induced cellular senescence and SASP through both protection from DNA damage and dominant-negative inhibition of full-length p53, leading to inhibition of Aβ-induced, astrocyte-mediated neurotoxicity. The results presented here demonstrate that Δ133p53α manipulation could modulate cellular senescence in the context of AD, possibly opening new therapeutic avenues.